Spatial Manipulation via Four-Wave Mixing in Five-Level Cold Atoms - Gan, Shoufei (Frontiers in Physics, 2022)
In a recent publication [S. Gan, Laser Phys. 31, 055401 (2021)], a scheme for controlling the vortex four-wave mixing (FWM) in a five-level atomic system has been put forward. Based on this work, we propose a new scheme for the spatial manipulation via four-wave mixing in a five-level atomic system when the radial index is considered. It is found that the phase and intensity of the FWM field can be spatially manipulated. More importantly, we show the superposition modes created by the interference between the FWM field and a same-frequency Gaussian beam, which can also be controlled via the corresponding parameters. Our research is helpful to understand and manipulate optical vortices and can be widely used in quantum computation and communication.